An observational study ascertaining the prevalence of bullae and blebs in young, healthy adults and its possible implications for scuba diving - Bresser, Max F.; Wingelaar, Thijs T.; Van Weering, Jaap A. F.; Bresser, Paul; Van Hulst, Rob A. (Frontiers in Physiology, 2024)
Introduction Intrapulmonary air-filled cavities, e.g., bullae, blebs, and cysts, are believed to contribute topulmonary barotrauma (PBT) and arterial gas embolism (AGE) in divers. However, literature is unclear about the prevalence of bullae in healthy adults, ranging from 2.3ꟷ33.8%. While this could in part be explained due to increasing quality of radiologic imaging, such as computed tomography (CT) scans, other methodological factors may also affect these findings. This study aims to ascertain the prevalence of bullae in young and healthy adults. Methods This single-center cross-sectional observational study re-assessed the CT scans of adults (aged 18ꟷ40) performed for a clinical suspicion for pulmonary embolism, from January 1st, 2016 to March 1st 2020. Presence of bullae was recorded in an electronic database. Chi-square and Fisher exact tests were used for statistical analyses. Additionally, a multivariate logistic regression analysis was performed to study the independent predictive value of identified risk factors. Results A total of 1014 cases were identified, of which 836 could be included. Distribution amongst age groups (18–25, 26–30, 31–35 and 36–40) was almost equally, however, 75% of the population was female. Of the male proportion, 41% smoked, compared to 27% in females. In 7.2% (95% CI 5.6–9.1) bullae were identified. The prevalence increased with increasing age (p<0.001), with odd ratios up to 5.347 (95% CI 2.164–13.213, p<0.001) in the oldest age group. Males and smokers had higher odds ratios for bullae of 2.460 (95% CI 1.144–4.208; p=0.001) and 3.406 (95% CI 1.878–6.157, p<0.001), respectively. Similar results were seen in the multivariate logistic regression analysis, where age, male sex and smoking were all statistically significant independent risk factors for bullae. Discussion Bullae were seen in 7.2% of a healthy population up to 40 years old. Increasing age, smoking, and being male were identified as statistically significant risk factors, both in independent and in multivariate logistic regression analyses. Our observations may warrant a re-evaluation of the contribution of bullae to PBT and AGE, as the latter two occur very rarely and bullae appear to be more frequently present than earlier assumed.